Intraocular lens materials and intraocular lenses

The intraocular lens material with a balanced monomer mixture addresses the challenges of flexibility, stability, and glistening by using specific mono(meth)acrylates and di(meth)acrylates, resulting in a lens that is stable, foldable, and resistant to glistening, improving surgical performance.

JP7609389B1Active Publication Date: 2025-01-07FULO JAPAN INC +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024531213
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-10-25
Filing Date
2024-01-29
Publication Date
2025-01-07
Estimated Expiration
2044-01-29

AI Technical Summary

Technical Problem

Existing intraocular lenses face challenges in achieving high refractive index, flexibility for folding, and stability within the eye while minimizing glistening and whitening, particularly in multifocal and toric lenses, due to issues with material selection and structural design.

Method used

An intraocular lens material comprising a monomer mixture of mono(meth)acrylates with aryl groups and di(meth)acrylates with alkylene oxide groups, balanced to achieve a high refractive index, sufficient flexibility, and elongation, with a compressive load on the support part, using specific ratios and properties to enhance stability and prevent glistening.

Benefits of technology

The solution results in an intraocular lens with improved stability, flexibility, and reduced glistening and whitening, allowing for easy folding and insertion, while maintaining high refractive index and compressive load, enhancing surgical efficacy and patient outcomes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609389000021
    Figure 0007609389000021
  • Figure 0007609389000022
    Figure 0007609389000022
  • Figure 0007609389000023
    Figure 0007609389000023
Patent Text Reader

Abstract

According to one aspect of the present invention, an intraocular lens material is provided. The intraocular lens material includes a mono(meth)acrylate (A) having an aryl group in its molecular structure, a mono(meth)acrylate (B) different from the mono(meth)acrylate (A) having an aryl group in its molecular structure, and a di(meth)acrylate (C) having an alkylene oxide group in its molecular structure. The content of the mono(meth)acrylate (A) in the intraocular lens material is 45 mol % or more and 70 mol % or less, and the total content of the mono(meth)acrylate (A) and the mono(meth)acrylate (B) is 85 mol % or more. The proportion of the di(meth)acrylate represented by the following general formula (I) in the di(meth)acrylate (C) is 60 mol % or more. [Formula 1] TIFF0007609389000020.tif22130 [In the formula, X is a methyl group or a hydrogen atom, and n is an integer of 12 or more and 30 or less.]
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an intraocular lens material and an intraocular lens. More specifically, the present invention relates to an intraocular lens material capable of producing an intraocular lens having a high refractive index, sufficient flexibility and elongation for folding the lens into a small size, and suppressing the occurrence of glistening and whitening, and an intraocular lens having a high haptic compression load even though the optical part and the haptic parts are made of the same material. [Background technology]

[0002] As intraocular lenses used to treat cataracts have become more common, soft intraocular lenses that can be inserted through small incisions have been developed with the aim of reducing postoperative astigmatism and surgical invasiveness, and are now widely used in clinical practice. Traditionally, intraocular lenses were only available as single-focus lenses that focused on either near or far objects, but recently, multifocal intraocular lenses designed to correct vision for both near and far objects, and toric intraocular lenses that correct pre-operative astigmatism have been developed and commercialized.

[0003] An intraocular lens includes an optic that corrects the patient's vision and haptics that hold the optic within the eye. The intraocular lens is folded small for insertion into the capsular bag through a corneal incision and placed in the appropriate position in the capsular bag. The folded intraocular lens then expands so that the haptics come into contact with the capsular bag and are held in the capsular bag by the haptics. The intraocular lens material for forming such an intraocular lens must have a high refractive index so that the thickness of the intraocular lens can be made small. In addition, the intraocular lens must be rolled or folded small so that it can be inserted into the eye through a small incision. In order to avoid cracking or breakage during this process, the intraocular lens material must be flexible and have a high elongation rate.

[0004] Next, after the intraocular lens is inserted into the eye, it is also necessary that the intraocular lens material does not suffer from so-called glistening or whitening, a phenomenon in which water trapped in the lens precipitates and coagulates, causing the water to appear as dots and significantly reducing the lens' transparency. Furthermore, even if the support part of the intraocular lens or the contact part in the capsular bag shrinks after surgery, the optical part of the intraocular lens rarely shifts significantly, but it may become slightly decentered or tilted over time. In particular, multifocal intraocular lenses and toric intraocular lenses need to be correctly inserted and fixed in the target position both during and after surgery, and it is important that the intraocular lens is highly stable in the capsular bag and does not rotate.

[0005] Here, intraocular lenses made of flexible materials are classified into two types: a three-piece type in which an optical portion is made of an acrylic material with excellent transparency and flexibility, and a loop-shaped wire made of PMMA (polymethyl methacrylate), PP (polypropylene), or PVDF (polyvinylidene fluoride) is attached as a support portion, and a one-piece type in which the optical portion and support portion are integrated into one body made of the same material. Three-piece intraocular lenses are characterized by the fact that the haptics are made of a material that is harder and more elastic than the optical part, so that the stress on the haptics is higher when compressed, and therefore the lenses are highly stable within the capsule. However, because the loops of the haptics are thin, they are unable to fully absorb the external force acting on the intraocular lens when the capsule contracts, making the optical part more likely to rotate, and when inserted into the capsule, depending on the orientation of the haptics (loops) that are hard and highly elastic, they can damage the capsule.

[0006] On the other hand, one-piece intraocular lenses are not only easy to insert into the lens capsule due to their structure, but also have high flexibility of the haptics, so there is no risk of damaging the lens capsule. In addition, the haptics of one-piece lenses can be made wider than those of three-piece lenses, so the optical part is less likely to rotate after surgery. However, one-piece intraocular lenses have soft haptics and low stress when compressed, so they tend to be less stable in the lens capsule than three-piece intraocular lenses. In one-piece intraocular lenses, in order to increase the stability within the lens capsule, it is sufficient to increase the force with which the support presses the eye tissue, and it has been proposed to configure the support with a main body made of a flexible material and a shaft made of an elastic material (see Patent Document 1). However, in Patent Document 1, since the shaft is embedded in the main body that configures the support, it is necessary to accurately align and fix the shaft to an appropriate location, which is a complicated process and not suitable for mass production.

[0007] Patent Document 2 proposes a polymer material and an intraocular lens containing a four-branched macromonomer containing a repeating unit of an ethylene oxide group. Here, the four-branched macromonomer containing a repeating unit of an ethylene oxide group is used for the purpose of suppressing glistening and whitening. However, since the component also serves as a crosslinking agent, the number of crosslinking points in the network polymer increases, and the elongation of the obtained polymer material tends to be low. Furthermore, in the examples, the components constituting the polymer material contain a relatively large amount of methacrylate monomers having aryl groups, but no consideration is given to the relationship between the types and amounts of these components used and the compressive load of the support portion of the intraocular lens. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2018-183197 A [Patent Document 2] JP 2019-210345 A Summary of the Invention [Problem to be solved by the invention]

[0009] In view of the above circumstances, the object of the present invention is to provide an intraocular lens material capable of producing an intraocular lens having a high refractive index, sufficient flexibility and elongation to allow the lens to be folded small, and suppressed occurrence of glistening and whitening, and to provide an intraocular lens having a high compressive load of the haptics and high stability within the eye, even though the optical part and the haptics are made of the same material. [Means for solving the problem]

[0010] According to one aspect of the present invention, an intraocular lens material is provided. The intraocular lens material includes a mono(meth)acrylate (A) having an aryl group in its molecular structure, a mono(meth)acrylate (B) different from the mono(meth)acrylate (A) having an aryl group in its molecular structure, and a di(meth)acrylate (C) having an alkylene oxide group in its molecular structure. The content of the mono(meth)acrylate (A) in the intraocular lens material is 45 mol % or more and 70 mol % or less, and the total content of the mono(meth)acrylate (A) and the mono(meth)acrylate (B) is 85 mol % or more. The proportion of the di(meth)acrylate represented by the following general formula (I) in the di(meth)acrylate (C) is 60 mol % or more. [ka] [In the formula, X is a methyl group or a hydrogen atom, and n is an integer of 12 or more and 30 or less.]

[0011] According to this aspect, it is possible to provide an intraocular lens material that can be used to produce an intraocular lens that has a high refractive index, sufficient flexibility and elongation to fold the lens small, and suppresses the occurrence of glistening and whitening, and an intraocular lens that has a high compressive load of the haptics and is highly stable within the eye, even though the optical part and the haptics are made of the same material. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a plan view showing the configuration of an intraocular lens. [Diagram 2] FIG. 2 is a diagram showing a state in which an intraocular lens is set on a stage of a compression load measuring device for a support part. [Diagram 3] FIG. 13 is a diagram showing a state in which the distance between the support portions of the intraocular lens is compressed to 10 mm. [Figure 4] FIG. 2 is a diagram showing the state in which the optical portion of the intraocular lens is set on a stage for measuring the compressive load of the optical portion. [Diagram 5] FIG. 2 shows the intraocular lens in a state in which the optical portion is compressed to 3 mm and folded in half. [Figure 6] 1 is a graph showing the relationship between the separation distance (compression distance) between support portions and the compression load in Examples 1 to 3 and Comparative Examples 1 and 2. [Figure 7] FIG. 11 is a plan view showing another configuration of the intraocular lens. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The intraocular lens material and the intraocular lens of the present invention will be described in detail below. <<Intraocular lens materials>> An intraocular lens material is a composition that can be used to prepare an intraocular lens, which comprises an optical portion that transmits light and a pair of support portions that protrude outward from opposing positions of the optical portion and support (hold) the optical portion within the eye.

[0014] This intraocular lens material contains a mono(meth)acrylate (A) having an aryl group in its molecular structure (hereinafter also referred to simply as "mono(meth)acrylate (A)"), a mono(meth)acrylate (B) which is different from the mono(meth)acrylate (A) and has an aryl group in its molecular structure (hereinafter also referred to simply as "mono(meth)acrylate (B)"), and a di(meth)acrylate (C) having an alkylene oxide group in its molecular structure (hereinafter also referred to simply as "di(meth)acrylate (C)").

[0015] Such an intraocular lens material is a mixture of monomers of mono(meth)acrylate (A), mono(meth)acrylate (B) and di(meth)acrylate (C). Therefore, hereinafter, the intraocular lens material is also referred to as a "monomer mixture." Furthermore, the monomer mixture may further contain any additives, such as a crosslinking monomer, a reactive monomer having ultraviolet absorbing properties, and a reactive monomer having coloring properties, as necessary. Each component will be described in turn below.

[0016] <Mono(meth)acrylate (A)> The mono(meth)acrylate (A) is a monomer that is blended into the monomer mixture for the purposes of imparting a sufficient elastic modulus to the intraocular lens and enabling the support to maintain a high compressive load. When a homopolymer is synthesized using mono(meth)acrylate (A), the glass transition temperature of the homopolymer of this mono(meth)acrylate (A) is preferably higher than the glass transition temperature of the homopolymer of mono(meth)acrylate (B) described below. With an intraocular lens material containing mono(meth)acrylates (A) and (B) having different properties, the glass transition temperature of the copolymer (hereinafter also simply referred to as "obtained copolymer"), which is a polymer obtained by polymerization of the intraocular lens material, can be appropriately adjusted by appropriately setting the quantitative ratio between them. As a result, the elastic modulus of the intraocular lens can be sufficiently increased.

[0017] The glass transition temperature of the homopolymer of the mono(meth)acrylate (A) is preferably about 40° C. or higher, and more preferably about 40° C. or higher and 70° C. or lower, in which case the glass transition temperature of the resulting copolymer can be more appropriately adjusted. The mono(meth)acrylate (A) is preferably a compound having one aryl group and one (meth)acryloyl group in one molecule. In this specification, the term "(meth)acryloyl group" means a methacryloyl group or an acryloyl group.

[0018] Specific examples of the mono(meth)acrylate (A) include, for example, 2-phenylethyl methacrylate, 2-phenoxyethyl methacrylate, benzyl methacrylate, and phenyl acrylate. Among these, the mono(meth)acrylate (A) is preferably 2-phenylethyl methacrylate, 2-phenoxyethyl methacrylate, or benzyl methacrylate. These compounds may be used alone or in combination of two or more. By using such a mono(meth)acrylate (A), the glass transition temperature of the resulting copolymer is easily increased.

[0019] The content of the mono(meth)acrylate (A) in the intraocular lens material is about 45 mol% or more and 70 mol% or less, more preferably about 50 mol% or more and 70 mol% or less, and even more preferably about 50 mol% or more and 68 mol% or less. When the content is expressed in mass%, the content of the mono(meth)acrylate (A) in the intraocular lens material is preferably about 40 mol% or more and 60 mol% or less, more preferably about 42 mol% or more and 60 mol% or less, and even more preferably about 45 mol% or more and 60 mol% or less. In this case, the elastic modulus of the intraocular lens is further increased, and the compressive load of the support can be further increased.

[0020] In this specification, the term "glass transition temperature (Tg)" refers to a value determined by differential scanning calorimetry, which will be described later. Also, "mol %" refers to the number of moles of a specific component in the total amount (100 mol %) of the number of moles of mono(meth)acrylate (A), the number of moles of mono(meth)acrylate (B) described below, the number of moles of di(meth)acrylate (C), and further the number of moles of crosslinkable monomer (D), reactive monomer (E) having ultraviolet absorbing properties, reactive monomer (F) having colorability, and (meth)acrylate (H) having an ethylene oxide group. Similarly, "mass %" refers to the mass of a specific component in the total amount (100 mass %) of the masses of these components ((A) to (F) and (H)).

[0021] <Mono(meth)acrylate (B)> The mono(meth)acrylate (B) is a monomer that is blended together with the mono(meth)acrylate (A) in the monomer mixture for the purpose of imparting a high refractive index to the intraocular lens, etc. The mono(meth)acrylate (B) is also a monomer used to adjust the glass transition temperature of the resulting copolymer. The glass transition temperature of the homopolymer of the mono(meth)acrylate (B) is preferably less than about 40° C., more preferably about 30° C. or less, and even more preferably about 20° C. or less. The glass transition temperature is preferably about −5° C. or more. By using such a mono(meth)acrylate (B), the glass transition temperature of the resulting copolymer can be more appropriately adjusted. The mono(meth)acrylate (B) is preferably a compound having one or two aryl groups and one (meth)acryloyl group in one molecule.

[0022] Specific examples of the mono(meth)acrylate (B) include, for example, 2-phenylethyl acrylate, 3-phenylpropyl (meth)acrylate, 4-phenylbutyl (meth)acrylate, 2-phenoxyethyl acrylate, 3-phenoxypropyl (meth)acrylate, 4-phenoxybutyl (meth)acrylate, benzyl acrylate, 3-phenoxybenzyl (meth)acrylate, 5-phenylpentyl (meth)acrylate, 6-phenylhexyl (meth)acrylate, 5-phenoxypentyl (meth)acrylate, 6-phenoxyhexyl (meth)acrylate, etc. Among these, the mono(meth)acrylate (B) is preferably 2-phenylethyl acrylate, 3-phenylpropyl methacrylate, 4-phenylbutyl methacrylate, 2-phenoxyethyl acrylate, or 3-phenoxybenzyl methacrylate. These compounds may be used alone or in combination of two or more. By using such a mono(meth)acrylate (B), it is easy to adjust the glass transition temperature of the resulting copolymer.

[0023] The total content of mono(meth)acrylate (A) and mono(meth)acrylate (B) in the intraocular lens material is about 85 mol% or more, more preferably about 90 mol% or more, and even more preferably about 95 mol% or more. When the content is expressed in mass%, the total content of mono(meth)acrylate (A) and mono(meth)acrylate (B) in the intraocular lens material is preferably about 80 mass% or more, more preferably about 82 mass% or more, and even more preferably about 85 mass% or more. By setting the contents of the mono(meth)acrylate (A) and the mono(meth)acrylate (B) within the above ranges, the glass transition temperature of the obtained copolymer can be suitably adjusted, and the refractive index of the intraocular lens can be increased while imparting flexibility that enables the intraocular lens to be folded compactly.

[0024] As described above, an intraocular lens has an optical part that corrects vision and haptics that hold the optical part inside the eye. The intraocular lens inserted into the eye is held in the lens capsule by the haptics expanding to contact the lens capsule. Therefore, in order to obtain an intraocular lens that is highly stable inside the eye, it is important to increase the force with which the haptics press against the lens capsule (i.e., the repulsive force of the haptics). Although the detailed mechanism is unclear, it has been revealed that the compressive load of the support part can be increased by using a certain amount of the mono(meth)acrylate (A). It is believed that the physical properties of the copolymer synthesized by radical polymerization are affected by the selection of the monomers constituting the copolymer, the amount of the monomers blended, and the network polymer structure. Therefore, it is believed that the compressive load of the support part is ultimately increased by the interaction of physical properties such as the glass transition temperature, mechanical strength, elongation, and stress of the copolymer, rather than by a single physical property.

[0025] <Di(meth)acrylate (C)> The di(meth)acrylate (C) is a monomer that is blended into the monomer mixture for the purposes of not only suppressing the occurrence of glistening and whitening of the intraocular lens, but also imparting sufficient flexibility and elongation to the intraocular lens so that it can be folded compactly. As represented by the following general formula, this di(meth)acrylate (C) is a monomer or macromonomer having a repeating unit of an alkylene oxide group and two (meth)acryloyl groups in its molecular structure. [ka] [In the formula, X is a methyl group or a hydrogen atom, R is an alkylene group, and l is an integer of 12 or more and 40 or less.]

[0026] In the above general formula, the value of l may or may not have a distribution. In addition, the fact that the value of l has no distribution means that, for example, when the value of l is 12, it is a single repeat number that does not include other values ​​(10, 11, 13, etc.). The repeat number l of the alkylene oxide group is preferably an integer of 12 to 38, more preferably an integer of 12 to 36. By setting l to a value equal to or greater than the above lower limit, it is possible to more reliably suppress the occurrence of glistening or whitening of the intraocular lens, and to impart excellent flexibility and elongation for folding the intraocular lens compactly. On the other hand, by setting l to the above upper limit or less, it is possible to increase compatibility with other monomers (A, B, D, E, F, and H), and to obtain a homogeneous monomer mixture (intraocular lens material).

[0027] In this specification, the term "average value" applies when there is a distribution in the repeating number in the alkylene oxide group of the di(meth)acrylate (C) and in the ethylene oxide group of the (meth)acrylate (H) having an ethylene oxide group other than the di(meth)acrylate (C) described below. Specifically, the "average value" is the average value of the di(meth)acrylate (C) or (meth)acrylate (H). 1 This refers to the value obtained by rounding off the number of repetitions obtained by calculating the peak integrated intensity ratio of alkylene oxide or ethylene oxide in H-NMR analysis to one decimal place.

[0028] As the di(meth)acrylate (C), for example, a di(meth)acrylate having a molecular weight of about 600 or more and 2,400 or less can be mentioned. In this specification, the term "molecular weight" means, in the case of the di(meth)acrylate (C) or the (meth)acrylate (H), the number average molecular weight calculated by gel permeation chromatography. As used herein, the term "macromonomer" refers to a monomer having a molecular weight of 800 or more. If the molecular structure of this di(meth)acrylate (C) is monofunctional, the elongation of the resulting copolymer becomes excessively large, which is undesirable since it deteriorates the shape recovery of the intraocular lens and makes it impossible to suppress glistening or whitening depending on the amount of the compounded material. Also, if it is trifunctional or more, the crosslinking points in the structure of the resulting copolymer become too many, which is undesirable since it extremely reduces the elongation of the intraocular lens, which causes cracks or breaks when the lens is folded compactly, or reduces the refractive index of the resulting copolymer, which makes it necessary to thicken the optical part.

[0029] The degree of hydrophilicity of the resulting copolymer can be adjusted depending on the type of alkylene oxide group of the di(meth)acrylate (C), which can further improve the effect of suppressing the occurrence of glistening and whitening of the intraocular lens. Examples of the alkylene oxide group of the di(meth)acrylate (C) include an ethylene oxide group and a propylene oxide group. The alkylene oxide group preferably contains an ethylene oxide group. Specifically, the alkylene oxide group is preferably an ethylene oxide group alone or a combination of an ethylene oxide group and a propylene oxide group. In this case, the hydrophilicity of the resulting copolymer can be further increased.

[0030] For example, a di(meth)acrylate having an ethylene oxide group alone is represented by the following general formula (I). [ka] [In the formula, X is a methyl group or a hydrogen atom, and n is an integer of 12 or more and 30 or less.] In the above general formula (I), n is preferably an integer of 13 or more and 28 or less, more preferably an integer of 14 or more and 26 or less, and even more preferably an integer of 15 or more and 26 or less.

[0031] Furthermore, for example, a di(meth)acrylate having an ethylene oxide group and a propylene oxide group is represented by the following general formula (II). [ka] [In the formula, X is a methyl group or a hydrogen atom, n1 and n2 each independently represent an integer of 4 or more and 15 or less, and m is an integer of 6 or more and 20 or less.] In the above general formula (II), n1 and n2 are each independently preferably an integer of 5 or more and 14 or less, more preferably an integer of 6 or more and 13 or less, and even more preferably an integer of 7 or more and 12 or less. Furthermore, m is preferably an integer of 7 or more and 20 or less, more preferably an integer of 8 or more and 19 or less, and even more preferably an integer of 9 or more and 18 or less.

[0032] The proportion of the di(meth)acrylate represented by the above general formula (I) in the di(meth)acrylate (C) is about 60 mol % or more, preferably about 70 mol % or more, more preferably about 80 mol % or more, even more preferably about 90 mol % or more, and may be about 100 mol %. In this case, the effect of suppressing the occurrence of glistening and whitening of the intraocular lens can be further improved. When the di(meth)acrylate (C) contains a di(meth)acrylate other than the di(meth)acrylate represented by the above general formula (I), the other di(meth)acrylate is preferably a di(meth)acrylate represented by the above general formula (II). That is, the di(meth)acrylate (C) preferably further contains a di(meth)acrylate represented by the following general formula (II). In this case, it becomes easier to adjust the degree of hydrophilicity of the obtained copolymer.

[0033] The content of the di(meth)acrylate (C) in the intraocular lens material is preferably about 0.5 mol% or more and about 3.5 mol% or less, more preferably about 1 mol% or more and about 3.5 mol% or less, and even more preferably about 1.5 mol% or more and about 3.5 mol% or less. When the content is expressed in mass%, the content of the di(meth)acrylate (C) in the intraocular lens material is preferably about 5 mass% or more and about 20 mass% or less, more preferably about 7 mass% or more and about 20 mass% or less, and even more preferably about 7 mass% or more and about 18 mass% or less. In this case, it is possible to further improve the effect of suppressing the occurrence of glistening and whitening of the intraocular lens, and further improve the effect of suppressing the occurrence of cracks and breaks when folded small by adjusting the elongation rate.

[0034] <Crosslinking Monomer (D)> The crosslinking monomer (D) is a type of auxiliary monomer that is mixed into the monomer mixture liquid for the purpose of adjusting the mechanical strength and elongation of the intraocular lens. Specific examples of the crosslinkable monomer (D) include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,3-propanediol di(meth)acrylate, 2,3-propanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate. Among these, the crosslinkable monomer (D) is preferably ethylene glycol dimethacrylate or 1,4-butanediol diacrylate. These compounds may be used alone or in combination of two or more.

[0035] The content of the crosslinkable monomer (D) in the intraocular lens material is preferably less than about 3 mol%, more preferably less than about 2.5 mol%, and even more preferably less than about 2 mol%. When the content is expressed in mass%, the content of the crosslinkable monomer (D) in the intraocular lens material is preferably about 2 mass% or less, more preferably about 1.5 mass% or less, and even more preferably about 1 mass% or less. By setting the content of the crosslinkable monomer (D) within the above range, it is possible to provide the intraocular lens with auxiliary mechanical strength, adjust the elongation rate of the intraocular lens, and suppress embrittlement.

[0036] <UV-absorbing reactive monomer (E)> The reactive monomer (E) having ultraviolet absorbing properties (hereinafter, also referred to simply as "reactive monomer (E)") is, for example, a monomer that has a structure capable of absorbing ultraviolet light and is blended into the monomer mixture for the purpose of imparting ultraviolet absorbing ability to the intraocular lens. Specific examples of the reactive monomer (E) include 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole, 2-hydroxy-4-(methacryloyloxy)benzophenone, 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole, 2-(2-hydroxy-3-(methacryloxyaminomethyl)-5-tert-octylphenyl)-2H-benzotriazole, 3-(3-(tert-butyl)-4-hydroxy-5-(5-methoxy-2H-benzo[d][1,2,3]triazol-2-yl)phenoxy)propyl methacrylate, etc. Among these, the reactive monomer (E) is preferably 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole or 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole. These compounds may be used alone or in combination of two or more.

[0037] The content of the reactive monomer (E) in the intraocular lens material is preferably about 0.5 mol% or less, and more preferably about 0.2 mol% to 0.4 mol%. When the content is expressed in mass%, the content of the reactive monomer (E) in the intraocular lens material is preferably about 1 mass% or less, and more preferably about 0.3 mass% to 0.6 mass%.

[0038] <Reactive monomer having coloring ability (F)> The reactive monomer (F) having coloring properties (hereinafter, also simply referred to as "reactive monomer (F)") is, for example, a monomer that has a structure capable of absorbing blue light and exhibits a yellow color, and is blended into a monomer mixture for the purpose of coloring an intraocular lens, etc. The reactive monomer (F) may be an azo-based, pyrazolone-based, or cyanine-based yellow colorant. Specific examples of the reactive monomer (F) include the yellow colorants described in JP-A-10-195324, JP-A-2000-290256, JP-A-2003-119226, JP-T-2008-520811, JP-T-2008-520352, and JP-T-2012-532244. All of the matters described in these publications are incorporated herein by reference.

[0039] The content of the reactive monomer (F) in the intraocular lens material is preferably about 0.03 mol% or less, and more preferably about 0.008 mol% to 0.025 mol%. When the content is expressed in mass%, the content of the reactive monomer (F) in the intraocular lens material is preferably about 0.05 mass% or less, and more preferably about 0.01 mass% to 0.04 mass%. The above-mentioned mono(meth)acrylate (A), (B) and di(meth)acrylate (C) are mixed with, if necessary, the crosslinkable monomer (D) and the reactive monomers (E) and (F), and further with the polymerization initiator (G), and the mixture is thoroughly stirred to obtain a homogeneous monomer mixture.

[0040] <Polymerization initiator (G)> As the polymerization initiator (G), either a thermal polymerization initiator or a photopolymerization initiator can be used. Examples of the thermal polymerization initiator include peroxides such as di(4-tert-butylcyclohexyl)peroxydicarbonate, di(3,5,5-trimethylhexanoyl)peroxide, dilauroyl peroxide, benzoyl peroxide, tert-hexylperoxy-2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, and tert-butylperoxy-2-ethylhexanoate, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(isobutyronitrile), dimethyl-2,2'-azobis(2-methylpropionate), 2,2'-azobis(2-methylbutyronitrile), dimethyl-1,1'-azobis(1-cyclohexanecarboxylate), and 1,1'-azobis(cyclohexane-1-carbonitrile).

[0041] Examples of the photopolymerization initiator include benzoin methyl ether, 1-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxy-2-phenylacetophenone, 2-hydroxy-2-methylpropiophenone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide. The content of the polymerization initiator (G) in the intraocular lens material is appropriately selected depending on the polymerization temperature in thermal polymerization, the irradiation wavelength and irradiation intensity of light in photopolymerization, etc., but is preferably about 0.1 mol % or more and 1 mol % or less with respect to the total amount (100 mol %) of the monomers (A) to (F) and (H). When the content is expressed in mass %, the content of the polymerization initiator (G) in the intraocular lens material is preferably about 0.2 mass % or more and 0.8 mass % or less.

[0042] <<Intraocular lenses>> FIG. 1 is a plan view showing the configuration of an intraocular lens. The intraocular lens 1 comprises an optical portion 2 that transmits light, and a pair of support portions 3 that protrude outward from opposing positions of the optical portion 2 and support the optical portion 2 within the eye. Each support portion 3 is curved in an arc shape. In this intraocular lens 1, both the optical portion 2 and the pair of support portions 3 are made of a copolymer, which is a polymer of intraocular lens material. The total length L of the intraocular lens 1 is preferably about 11 mm or more and 15 mm or less, and more preferably about 12 mm or more and 14 mm or less. The diameter D of the optical part 2 is preferably about 5 mm to 7 mm, more preferably about 5.5 mm to 6.5 mm, and the central thickness of the optical part 2 is preferably about 0.4 mm to 0.9 mm, more preferably about 0.4 mm to 0.8 mm.

[0043] The width W1 of the support 3 on the optical section 2 side is designed to be larger than the width W2 of the support 3 on the opposite side to the optical section 2. Specifically, the width W1 of the support 3 on the optical section 2 side is preferably about 0.4 mm or more and 0.7 mm or less, and more preferably about 0.5 mm or more and 0.65 mm or less. On the other hand, the width W2 of the support 3 on the side opposite the optical section 2 is preferably about 0.3 mm or more and 0.6 mm or less, and more preferably about 0.3 mm or more and 0.4 mm or less. The thickness of the support portion 3 is preferably about 0.25 mm or more and 0.45 mm or less, and more preferably about 0.3 mm or more and 0.4 mm or less. The optical part 2 and the pair of haptics 3 may be fabricated separately from a copolymer (polymerization of intraocular lens material) and then bonded together, but it is preferable to form them integrally from a copolymer. By using the intraocular lens material described above, the optical part 2 and haptics 3 having the required characteristics can be obtained in one batch.

[0044] The elongation of the copolymer (polymer of intraocular lens material) at 23° C. is preferably about 150% or more, more preferably about 200% or more, and even more preferably about 250% or more. From the viewpoint of the shape recovery of the intraocular lens 1, the elongation of the copolymer at 23° C. is preferably about 600% or less. This makes it possible to suitably prevent the occurrence of cracks or breaks when the intraocular lens 1 is folded compactly, and allows it to be inserted into the lens capsule through a small incision. In this specification, the term "elongation" refers to the elongation of a rectangular test piece formed from the intraocular lens material to be tested. For example, "having an elongation rate of 200%" means that when a rectangular test piece having a total length of 15 mm, width of 1 mm, and thickness of 0.35 mm is processed and pulled until it breaks at a test speed of 100 mm / min under a test environment of 23°C and 50%, with a grip distance of 6 mm, the grip distance at the time of break is 18 mm.

[0045] The glass transition temperature of the copolymer (polymerization product of intraocular lens material) is preferably about 3°C ​​or higher and lower than 17°C, more preferably about 4°C or higher and lower than 17°C, and even more preferably about 5°C or higher and lower than 17°C. When the glass transition temperature of the copolymer is 3° C. or higher, it becomes easy to process it into the intraocular lens 1. On the other hand, when the glass transition temperature of the copolymer is less than 17° C., it becomes possible to fold the intraocular lens 1 with a small force, and further, it is possible to prevent a delay in the time until the lens returns to its original shape inside the eye.

[0046] The intraocular lens 1 has a higher compressive load of the haptics 3 than conventional intraocular lens materials. When the pair of haptics 3 of the intraocular lens 1 are brought close to each other so that the maximum separation distance between them is 13 mm to 10 mm, the load measured at each haptic 3 is preferably about 0.35 mN or more, more preferably about 0.36 mN or more, and even more preferably about 0.37 mN or more. The upper limit of the compressive load of the haptics 3 is preferably 1.8 mN, which is equivalent to the compressive load of the haptics of a 3P-type intraocular lens whose haptic material is made of PMMA. If the compressive load of the haptics 3 is about 0.35 mN or more, the compressive load is higher than that of conventional 1P-type intraocular lenses, and therefore it is possible to increase the stability of the intraocular lens 1 within the lens capsule. On the other hand, if the compressive load of the haptics 3 is about 1.8 mN or less, it is possible to suitably prevent the haptics 3 from damaging the lens capsule when the intraocular lens 1 is inserted.

[0047] When the copolymer (polymerization product of intraocular lens material) is in a dry state and its refractive index is measured at 23°C with an Abbe refractometer using e-line (546.1 nm), it is preferably at least about 1.535, more preferably at least about 1.540, and even more preferably at least about 1.545. By making the refractive index 1.535 or more, it is possible to reduce the central thickness of the optical part 2, which makes it easier to fold the intraocular lens 1. There are no particular limitations on the upper limit of the refractive index, but considering that the Abbe number tends to decrease as the refractive index increases, the upper limit is preferably 1.570.

[0048] When the intraocular lens is in a dry state and the optical portion 2 is folded in half at 23°C, the load (compressive load) is preferably about 30 gf or more and 800 gf or less, more preferably about 30 gf or more and 750 gf or less, and even more preferably about 30 gf or more and 700 gf or less. When an injector is used to simplify insertion of the intraocular lens 1 into the eye, if the compression load is 30 gf or more, the optical part 2 is less likely to twist when the intraocular lens 1 is ejected, and it is possible to bend it neatly. On the other hand, if the compression load is 800 gf or less, the user can eject the intraocular lens 1 with a small force.

[0049] The water content of the copolymer (polymer of intraocular lens material) in physiological saline at 23°C is preferably about 0.5% or more and 3% or less, more preferably about 0.5% or more and 2.9% or less, and even more preferably about 0.5% or more and 2.8% or less. By making the water content of the intraocular lens 1 about 0.5% or more, it is possible to more reliably prevent the occurrence of glistening or whitening of the intraocular lens 1. On the other hand, by making the water content of the intraocular lens 1 about 3% or less, it is possible to prevent the decrease in the refractive index of the intraocular lens 1 due to water content.

[0050] The intraocular lens 1 has high resistance to glistening and whitening. Here, the resistance to glistening and whitening is evaluated by the following procedure. First, an intraocular lens 1 having an optical part 2 with a diameter of 6.0 mm and a central thickness of 0.6 mm to 0.7 mm is immersed in physiological saline at 45° C. for 24 hours or more. Next, the intraocular lens 1 is left to stand for 2 hours while immersed in the physiological saline in an environment set to 23° C. Thereafter, the appearance (transparency) of the intraocular lens 1 is observed at a magnification of 20 times or more using, for example, a stereomicroscope (Nikon Solutions Corporation, “SMZ-745T”).

[0051] In this specification, "glistenings" refers to a state in which several to several tens of water particles having a particle size of approximately 1 μm to 10 μm are generated in intraocular lens 1, but there is substantially no decrease in the transparency of intraocular lens 1. On the other hand, "whitening" refers to a state in which the surface of the intraocular lens 1 appears misty and white due to the aggregation of a large number of minute water particles having an average particle size of 100 nm.

[0052] The evaluation of glistening and whitening is based on the temperature changes inside the eye that are expected to occur during ophthalmic surgery in which intraocular lens 1 is actually inserted into a human eye, or the temperature changes in the living environment after intraocular lens 1 is inserted into the eye. It is believed that glistening and whitening occur in the intraocular lens 1 due to this temperature change in the body. In general, in the case of an intraocular lens 1 with a low water content, the higher the temperature, the higher the water content. Therefore, evaluation of glistening and whitening over a wider range of temperature changes (23°C or higher and 45°C or lower) can be said to be carried out under more severe conditions. With the intraocular lens 1, glistening and whitening are unlikely to occur even under such severe conditions.

[0053] The intraocular lens 1 as described above can be produced as follows. First, a monomer mixture is poured into a mold for producing an intraocular lens that corresponds to the shape of the intraocular lens 1 to be produced, and then polymerized. This mold is a laminated mold with a curved recess formed therein, and is made of a material such as a metal material, a glass or quartz material, or a resin material. However, it is preferable that the material be one that allows easy peeling of the polymer of the monomer mixture (intraocular lens material or intraocular lens 1) from the mold and has excellent solvent resistance and heat resistance. A resin mold is preferable because it is easy to mold and can be molded into a shape required for the desired lens design.

[0054] The resin material is preferably selected from those having a small mold shrinkage rate, good surface transferability from a metal molding die, and excellent dimensional accuracy, solvent resistance, and heat resistance. In particular, polypropylene is preferred as the resin material because it is inexpensive and easily available. However, the resin material is not limited to polypropylene, and for example, polyethylene, polyacetal, polyethylene terephthalate, cycloolefin polymer, polymethylpentene, ethylene-vinyl alcohol copolymer, etc. may be used. When injecting the monomer mixture liquid, a mold immediately after molding may be used, or a mold that has been stored for 24 hours or more and 72 hours or less to stabilize the shape (curvature) of the curved recess may be used.

[0055] Furthermore, before using the mold, the pressure may be sufficiently reduced to remove substances that affect the radical polymerization reaction, such as moisture and oxygen, from the mold surface, and the mold may be purged with an inert gas, such as nitrogen gas or argon gas, before the monomer mixture is injected into the mold. Alternatively, a simpler method may be used, such as using a device such as a gas filter gun to spray an inert gas, such as nitrogen gas or argon gas, onto the mold surface, and then the monomer mixture is injected into the mold. Furthermore, when injecting the monomer mixture, the monomer mixture may be used after previously bubbling it with an inert gas such as nitrogen gas or argon gas to remove oxygen dissolved in the monomer mixture, or it may be used without removing the dissolved oxygen.

[0056] Examples of the polymerization method include a thermal polymerization method in which a thermal polymerization initiator is added to a monomer mixture and the mixture is heated, and a photopolymerization method in which a photopolymerization initiator is added to a monomer mixture and the mixture is irradiated with ultraviolet light or visible light. When using the thermal polymerization method, the mold is placed in a polymerization apparatus and then heated stepwise within a temperature range of from room temperature to about 120°C for about 10 to 48 hours, or the mold is placed in a polymerization apparatus previously set to a constant temperature (about 100°C to 120°C) and heated for about 1 to 10 hours. The atmosphere in which thermal polymerization is carried out is preferably an inert gas atmosphere such as nitrogen or argon gas. By carrying out thermal polymerization in such an atmosphere, the polymerization rate of the monomer can be improved and the amount of unpolymerized monomer can be reduced. In this case, the pressure in the polymerization apparatus is preferably atmospheric pressure or pressurized (about 0.196 MPa or less).

[0057] When the photopolymerization method is used, the wavelength of the irradiated light is not particularly limited since it is appropriately selected depending on the characteristics of the photopolymerization initiator added. Specific examples of lamps used for irradiating light include lamps having strong peaks in the wavelength range of 200 nm or more and 280 nm or less and 350 nm or less, lamps that emphasize wavelengths in the range of 350 nm or more and 400 nm or less, lamps that emphasize wavelengths in the range of 400 nm or more and 425 nm or less with a wavelength of 420 nm as the center, and lamps that emphasize wavelengths in the range of 400 nm or more and 450 nm or less. The light irradiation intensity varies depending on the light receiving area of ​​the measuring device, but for example, it is 1 mW / cm 2 More than 100mW / cm 2 It is preferable that the temperature is about the same or less.

[0058] The light irradiation time (polymerization time) is not particularly limited since it is appropriately set according to the light irradiation intensity. For example, 2 More than 100mW / cm 2 When the irradiation time is about 5 minutes or more and about 60 minutes or less, the irradiation time is preferably about 5 minutes or more and about 60 minutes or less. In addition, the atmosphere in which the photopolymerization is carried out is preferably an inert gas atmosphere such as nitrogen or argon gas. By carrying out the photopolymerization in such an atmosphere, the polymerization rate of the monomer can be improved and the amount of unpolymerized monomer can be reduced.

[0059] After the monomer mixture liquid has been cured by thermal polymerization or photopolymerization, it is preferable to carry out a reheating treatment in order to further reduce the amount of unpolymerized monomer. In this reheating process, first, the upper part of the mold where polymerization has been completed is removed, and the mold is placed in a heat treatment device with the polymerized product (cured product) of the monomer mixture liquid contained in the lower part. Next, after the temperature reaches a preset temperature in the range from room temperature to 115°C to 125°C in stages, it is heated continuously at that temperature for about 12 hours to 48 hours, and then cooled to room temperature. By carrying out this reheating treatment, it is possible to reduce the amount of unpolymerized monomer remaining in the polymer of the monomer mixture liquid to near the detection limit (approximately less than 1 μg / mL) in quantitative analysis by gas chromatography or high performance liquid chromatography.

[0060] When carrying out this reheating treatment, the unpolymerized monomers can be efficiently removed from the polymer of the monomer mixture liquid by continuously flowing in and out a constant flow rate of air or nitrogen gas into the heat treatment device. The efficiency of removing the unpolymerized monomers increases as the flow rate of the gas flowing into the heat treatment device increases, but a flow rate of about 10 L / min to 100 L / min is preferred. After polymerization of the monomer mixture, the polymerized product of the monomer mixture is removed from the mold, or without removing the polymerized product of the monomer mixture from the mold (i.e., while the polymerized product of the monomer mixture is contained within the mold), the polymerized product of the monomer mixture is cut at a low temperature and, in some cases, polished, to be processed into a desired shape (for example, the shape of the intraocular lens itself).

[0061] In another method, the monomer mixture is polymerized in a suitable mold or container to produce a polymer of the monomer mixture in a desired shape such as a rod, block, or plate, and then the polymer of the monomer mixture is cut at a low temperature and, in some cases, polished to form a desired shape. Therefore, the polymer of the monomer mixture before processing can also be considered as an intraocular lens material. Alternatively, the monomer mixture may be injected into a mold having the final shape of the intraocular lens, and after polymerization and reheating, the polymerized product of the monomer mixture may be removed and used as an intraocular lens as is without cutting or polishing. Furthermore, the surface of the optical part 2 of the intraocular lens 1 may be subjected to a cleaning treatment using low-temperature plasma treatment, atmospheric pressure plasma treatment, ultraviolet light, etc. By such a treatment, the cleanliness and cell adhesiveness of the surface of the optical part 2 of the intraocular lens 1 can be improved.

[0062] Next, other configurations of the intraocular lens will be described. FIG. 7 is a plan view showing another configuration of the intraocular lens. The intraocular lens 1 shown in FIG. 7 will be described below, focusing on the differences from the intraocular lens 1 shown in FIG. 1, and a description of the similar points will be omitted. The intraocular lens 1 shown in FIG. 7 is similar to the intraocular lens 1 shown in FIG. 1, except that the shape of each haptic portion 3 is different.

[0063] Each support portion 3 has, midway in the longitudinal direction, a wide portion 31 with an increased width, which makes it possible to increase the mechanical strength of each support portion 3 while maintaining its ease of deformation. In addition, the tip portion 32 (the end portion opposite the optical portion 2) of each support portion 3 is rounded. This makes it difficult for each support portion 3 to damage the lens capsule when inserting the intraocular lens 1 into the lens capsule, regardless of the orientation of the support portion 3. Furthermore, it may be provided in the following aspects:

[0064] (1) An intraocular lens material comprising a mono(meth)acrylate (A) having an aryl group in its molecular structure, a mono(meth)acrylate (B) different from the mono(meth)acrylate (A) and having an aryl group in its molecular structure, and a di(meth)acrylate (C) having an alkylene oxide group in its molecular structure, wherein the content of the mono(meth)acrylate (A) in the intraocular lens material is 45 mol % or more and 70 mol % or less, the total content of the mono(meth)acrylate (A) and the mono(meth)acrylate (B) is 85 mol % or more, and a proportion of a di(meth)acrylate represented by the following general formula (I) in the di(meth)acrylate (C) is 60 mol % or more. [ka] [In the formula, X is a methyl group or a hydrogen atom, and n is an integer of 12 or more and 30 or less.]

[0065] (2) The intraocular lens material according to (1) above, wherein the content of the di(meth)acrylate (C) in the intraocular lens material is 0.5 mol % or more and 3.5 mol % or less.

[0066] (3) The intraocular lens material according to (1) or (2) above, wherein the glass transition temperature of the homopolymer of the mono(meth)acrylate (A) is higher than the glass transition temperature of the homopolymer of the mono(meth)acrylate (B).

[0067] (4) The intraocular lens material according to any one of (1) to (3) above, wherein the homopolymer of the mono(meth)acrylate (A) has a glass transition temperature of 40° C. or higher.

[0068] (5) The intraocular lens material according to any one of (1) to (4) above, wherein the homopolymer of the mono(meth)acrylate (B) has a glass transition temperature of less than 40°C.

[0069] (6) The intraocular lens material according to any one of (1) to (5) above, wherein the alkylene oxide group of the di(meth)acrylate (C) contains an ethylene oxide group.

[0070] (7) The intraocular lens material according to (6) above, wherein the di(meth)acrylate (C) further contains a di(meth)acrylate represented by the following general formula (II): [ka] [In the formula, X is a methyl group or a hydrogen atom, n1 and n2 each independently represent an integer of 4 or more and 15 or less, and m is an integer of 6 or more and 20 or less.]

[0071] (8) The intraocular lens material according to any one of (1) to (7) above, wherein the elongation of the polymer of the intraocular lens material at 23° C. is 150% or more.

[0072] (9) The intraocular lens material according to any one of (1) to (8) above, wherein the glass transition temperature of the polymer of the intraocular lens material is 3°C or higher and lower than 17°C.

[0073] (10) An intraocular lens comprising an optical portion that transmits light and a pair of support portions that protrude outward from opposing positions of the optical portion and support the optical portion within the eye, wherein both the optical portion and the pair of support portions are made of a polymer of the intraocular lens material described in any one of (1) to (9) above.

[0074] (11) The intraocular lens according to (10) above, wherein the optical portion and the pair of support portions are integrally formed from the polymer.

[0075] (12) The intraocular lens according to (10) or (11) above, wherein when the pair of support portions are brought closer together so that the maximum separation distance between them is from 13 mm to 10 mm, the load measured at each of the support portions is 0.35 mN or more. Of course, this is not the case.

[0076] As described above, various embodiments of the present invention have been described, but these are presented as examples and do not limit the scope of the invention in any way. The novel embodiments can be embodied in various other forms, and various omissions, substitutions, and modifications can be made without departing from the gist of the invention. The embodiments and modifications thereof are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. EXAMPLES

[0077] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. 1.Ingredients used The names and abbreviations of compounds used in the following Examples and Comparative Examples are shown below.

[0078] 1-1. Mono(meth)acrylate having an aryl group in the molecular structure (A) PE-MA: 2-phenylethyl methacrylate [Molecular weight: 190, homopolymer Tg: 42.3℃] PO-MA: 2-phenoxyethyl methacrylate [Molecular weight: 206, homopolymer Tg: 48.8℃] BZ-MA: Benzyl methacrylate [Molecular weight: 176, homopolymer Tg: 65.3℃]

[0079] 1-2. Mono(meth)acrylate having an aryl group in the molecular structure (B) PPr-MA: 3-phenylpropyl methacrylate [Molecular weight: 204, homopolymer Tg: 17.8℃] PB-MA: 4-phenylbutyl methacrylate [Molecular weight: 218, homopolymer Tg: 4.0℃] ·PE-A: 2-Phenylethyl acrylate [Molecular weight: 176, homopolymer Tg: -4.0℃] PO-A: 2-phenoxyethyl acrylate [Molecular weight: 192, homopolymer Tg: 10.0] POB-A: 3-phenoxybenzyl acrylate [Molecular weight: 254, homopolymer Tg: 10.7℃]

[0080] 1-3. Di(meth)acrylate having an alkylene oxide group (C) ·P600DMA : Polyethylene glycol dimethacrylate [Molecular weight: 750, average number of repeating ethylene oxide groups is 13] ·P1000DMA: Polyethylene glycol dimethacrylate [Molecular weight: 1136, average number of repeating ethylene oxide groups is 23] 40PDC-1700B: Polyethylene glycol-polypropylene glycol dimethacrylate The 40PDC-1700B is expressed by the following formula: X is a methyl group; m is about 18, n1 and n2 are each about 9, and the molecular weight is 2007. [ka]

[0081] 1-4. Crosslinking monomer (D) EDMA: Ethylene glycol dimethacrylate [molecular weight: 198] BDDA: 1,4-butanediol diacrylate [molecular weight: 198]

[0082] 1-5. UV-absorbing reactive monomer (E) ·Norbloc: 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole [molecular weight: 323] o-MTP: 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole [molecular weight: 279]

[0083] 1-6. Colorable reactive monomers (F) ·MOAB: trans-4-(phenylazo)phenyl methacrylate [molecular weight: 266]

[0084] 1-7. Polymerization initiator (G) AIBN: 2,2'-Azobisisobutyronitrile [Molecular weight: 164] ·t-BPO: tert-Butyl peroxyoctoate [Molecular weight: 216] Perkadox: Bis(4-tert-butylcyclohexyl) peroxydicarbonate [Molecular weight: 399] ·BP: Benzoyl peroxide [molecular weight: 242]

[0085] 1-8. (Meth)acrylates (H) having an ethylene oxide group other than di(meth)acrylates (C) ·P200MMA: Methoxytetraethylene glycol methacrylate [Molecular weight: 287, average number of repeating ethylene oxide groups is 4] ·P400DA: Polyethylene glycol diacrylate [Molecular weight: 522, average number of repeating ethylene oxide groups is 9] · 4-ArmPEG35: Polyethoxylated tetramethylolmethane tetraacrylate [Molecular weight: 1892]

[0086] 4-ArmPEG35 is a macromonomer represented by the following formula (D1) in which the total number of repetitions (average value) of l, m, n, and o is 35. [ka]

[0087] 2. Preparation of Homopolymer (Homopolymer 1) First, 10 g of PE-MA and 0.04 g of AIBN (0.46 mol %, 0.4 mass % relative to PE-MA) were placed in a 20 mL glass bottle and stirred at room temperature for approximately 18 hours. Next, this monomer mixture was poured into a mold (made of polypropylene) for producing a coin-shaped polymer with a final shape of 16 mm in diameter and 0.6 mm in thickness, and the upper and lower halves were assembled. Next, this mold was placed in a polymerization apparatus and polymerization was carried out according to the following schedule.

[0088] [Table 1]

[0089] After polymerization, only the upper part of the mold was removed, leaving the polymerized material contained in the lower part. Next, the mold was placed in a heat treatment device and reheated according to the schedule below to obtain a plate-shaped polymer. [Table 2]

[0090] (Homopolymer 2-8) Similarly, 10 g of PO-MA, BZ-MA, PPr-MA, PB-MA, PE-A, PO-A or POB-A and 0.04 g of AIBN were weighed out and treated in the same manner as for homopolymer 1 to prepare a disk-shaped polymer.

[0091] 3. Measurement of glass transition temperature (Tg) First, a test specimen was extracted from the disk-shaped polymer obtained above using a biopsy trephine with a diameter of 5 mm. Next, the test piece was placed in close contact with the bottom of an aluminum container used for differential scanning calorimetry and sealed. At this time, the mass of the test piece was about 10 mg or more and 13 mg or less. Next, using an empty aluminum container as a reference material, the glass transition temperature was measured using a DSC3500 Sirius manufactured by NETZSCH according to the following schedule.

[0092] [Table 3]

[0093] From the obtained DSC chart, the midpoint glass transition temperature was determined as the glass transition temperature of the homopolymer. Note that, in order to eliminate a certain amount of thermal strain, the second heating data (Step 8 data in Table 3) was used for analysis. As a result, the glass transition temperatures of the respective homopolymers were as follows:

[0094] [Table 4]

[0095] 4. Preparation of Intraocular Lens Example 1 The following amounts of PE-MA, PE-A, P1000DMA, Norbloc, MOAB, and AIBN were weighed out and placed in a 20 mL glass bottle, and stirred at room temperature for about 18 hours to prepare a monomer mixture.

[0096] PE-MA: 5.520 g (58.87 mol%, 55.20 mass%) PE-A: 3.387 g (39.00 mol%, 33.87 mass%) P1000DMA: 1.054g (1.88 mol%, 10.54 wt%) Norbloc: 0.0375g (0.235 mol%, 0.375 mass%) MOAB: 0.00197g (0.015 mol%, 0.0197 mass%) AIBN: 0.04 g (0.494 mol%, 0.40 mass% based on the total amount of PE-MA, PE-A, P1000DMA, Norbloc and MOAB)

[0097] Next, this monomer mixture was injected into a mold (made of polypropylene) for producing an intraocular lens with a refractive power of +20.0D, a mold (made of polypropylene) for producing a coin-shaped polymer with a final shape of 16.5 mm in diameter and 0.6 mm in thickness, and another mold (made of polypropylene) for producing a coin-shaped polymer with a final shape of 16 mm in diameter and 0.35 mm in thickness, and the upper mold was assembled. Thereafter, the mold was placed in a polymerization apparatus, and polymerization and reheat treatment were carried out in the same manner as for homopolymer 1, to obtain an intraocular lens.

[0098] (Examples 2 and 3) An intraocular lens was produced in the same manner as in Example 1, except that the monomer mixture shown in Table 5 was prepared. (Comparative Examples 1 and 2) An intraocular lens was produced in the same manner as in Example 1, except that the monomer mixture shown in Table 5 was prepared.

[0099] 5. Measurement and Evaluation For the intraocular lenses obtained in each Example and Comparative Example, the glass transition temperature of the copolymer, the water content, the compressive load of the support, the refractive index, the tensile breaking elongation, the compressive load of the optical part, and glistening / whitening were evaluated.

[0100] 5-1. Measurement of the glass transition temperature (Tg) of copolymers In measuring the glass transition temperature of the copolymer, a test piece was taken out from a coin-shaped polymer of intraocular lens material having a diameter of 16.5 mm and a thickness of 0.6 mm using a biopsy trephine having a diameter of 5 mm. The glass transition temperature of this test piece was measured in the same manner as in "3. Measurement of glass transition temperature (Tg)" above.

[0101] 5-2. Moisture content measurement In the measurement of the water content, the unprocessed cured intraocular lens material produced in a mold for manufacturing intraocular lenses was used as a test specimen as it was. The test piece was then placed in a low-temperature vacuum dryer set at 60°C ± 5°C and dried under vacuum conditions (1 mmHg or more and 2 mmHg or less) for 2 hours (2 hours ± 1 hour). Next, the test piece was placed in a desiccator and cooled to room temperature, after which the mass was measured to one decimal place. This operation was repeated until the mass of the test piece became constant within ± 0.1 mg, and this was taken as the dry mass (mass: Wd).

[0102] The test pieces with known masses were placed one by one in embedding cassettes with identification numbers and then placed in a glass container containing 500 mL of physiological saline. This glass container was immersed in a water tank previously set at 23°C±1°C for 72 hours±1 hour. After immersion for a predetermined time, the test piece was taken out, the moisture on the surface was wiped off with a clean cloth, and the mass of the test piece was measured to one decimal place (mass Ww). After all measurements were completed, the moisture content was calculated according to the following formula. Moisture content (%)={(Ww-Wd) / Ww}×100

[0103] 5-3. Measurement of compressive load on support In the measurement of the compressive load of the support, an intraocular lens obtained by processing a polymerized material for an intraocular lens produced in a mold for manufacturing an intraocular lens was used. The specifications of the intraocular lens were as follows: Total length of intraocular lens L: 13.0mm Optical diameter D: 6.0mm, center thickness: 0.65mm Width of support on the optical side W1: 0.65mm, width on the opposite side to the optical side W2: 0.35mm, thickness: 0.35mm

[0104] The compression load of the support was measured in accordance with ISO11979-3:2012. Fig. 2 is a diagram showing a state in which the intraocular lens is set on a stage of a support compression load measuring device, and Fig. 3 is a diagram showing a state in which the distance between the support parts of the intraocular lens is compressed to 10 mm. Specifically, the intraocular lens 1 was set on the stage 10 of a measuring device for the compressive load of the haptic parts 3 (see FIG. 2), and compressed from 13.0 mm to 10.0 mm (see FIG. 3) to measure the stress accompanying the deformation of the haptic parts 3. The load (mN) at that time was taken as the compressive load of the haptic parts 3. The results were evaluated based on the load when compressed to 10.0 mm, and the measurement was performed in distilled water at 37°C.

[0105] 5-4. Refractive index measurement In measuring the refractive index, a rectangular test piece 10 mm wide and 15 mm long was cut out from a coin-shaped polymer of intraocular lens material 16.5 mm in diameter and 0.6 mm in thickness. The refractive index of this test piece at 23° C. with e-line (546.1 nm) was measured using a multi-wavelength Abbe refractometer (manufactured by Atago Co., Ltd., “DR-M2”).

[0106] 5-5. Measurement of tensile elongation at break In the measurement of the tensile elongation at break, a rectangular test piece having a length of 15 mm and a width of 1 mm was cut out from a coin-shaped polymer of the intraocular lens material having a diameter of 16.5 mm and a thickness of 0.35 mm. The test piece was then clamped by the clamping tools of a universal material testing machine (Instron Japan, "3342"). The distance between the clamping tools was 6 mm. The test piece was pulled at a speed of 100 mm / min in an environment of 23°C and 50% humidity, and the tensile elongation at break was calculated from the elongation at break according to the following formula.

[0107] (calculation formula) EB = (L-L0) / L0 x 100 EB: Elongation (tensile breaking elongation) (%) L: Distance between grippers at break (mm) L0: Original grip distance of the test piece (mm)

[0108] 5-6. Measurement of compressive load on the optical part To measure the compressive load of the optical portion, a polymerized material for intraocular lenses prepared using a mold for intraocular lens manufacturing was processed into an intraocular lens, the base of the support portion was cut off from the obtained intraocular lens, and only the portion corresponding to the optical portion was used as the test specimen. Fig. 4 is a diagram showing a state in which the optical portion of the intraocular lens is set on a stage for measuring the compressive load of the optical portion. Fig. 5 is a diagram showing a state in which the optical portion of the intraocular lens is compressed to 3 mm and folded in half. The test piece was then fixed vertically on the stage of a universal material testing machine (Instron Japan, "3342") (see Fig. 4). In this state, the test piece was folded from 6 mm to 3 mm at a speed of 100 mm / min in an environment of 23°C and 50% humidity (see Fig. 5), and the maximum load (gf) at this time was taken as the compression load of the optical part.

[0109] 5-7. Glistening / Whitening Evaluation In the evaluation of glistening / whitening, an intraocular lens was used, which was obtained by processing a polymerized material for an intraocular lens produced in a mold for intraocular lens production. The specifications of the intraocular lens were as follows: Total length of intraocular lens L: 13.0mm Optical diameter D: 6.0mm, center thickness: 0.65mm Width of support on the optical side W1: 0.65mm, width on the opposite side to the optical side W2: 0.35mm, thickness: 0.35mm

[0110] The test piece was then immersed in physiological saline at 45° C. for 48 hours, and then allowed to stand for 2 hours in an environment set at 23° C. Thereafter, the appearance (transparency) of the test piece in the physiological saline was observed at a magnification of 50 times using a stereomicroscope (Nikon Solutions Corporation, “SMZ-745T”), and evaluated according to the following evaluation criteria. <Evaluation criteria> G (Good): The test piece has excellent transparency, and no water particles are observed inside. B (Bad): The test piece is cloudy (whitening) or transparent with water particles found inside (glistening).

[0111] The results are shown in Table 5 below and in FIG. [Table 5]

[0112] In Table 5, the units of the contents of the monomers and polymerization initiators are mol% in the upper row and % by mass in parentheses in the lower row. The content of the polymerization initiator (G) is expressed as a percentage relative to the total amount of moles (100 mol%) or the total amount of mass (100 mass%) of the monomers (A) to (C), (E) and (F). FIG. 6 is a graph showing the relationship between the separation distance (compression distance) between the support portions and the compression load in Examples 1 to 3 and Comparative Examples 1 and 2. In FIG. As shown in Table 5 and FIG. 6, the intraocular lenses obtained in Examples 1 to 3 had copolymer glass transition temperatures of 9.0°C, 14.2°C, and 16.4°C, tensile elongations at break of 325%, 370%, and 394%, and support compression loads of 0.689 mN, 0.733 mN, and 0.811 mN. FIG. 6 also shows the value of the compressive load (1.8 mN) of the haptics of a 3P type intraocular lens whose haptics are made of polymethyl methacrylate (PMMA).

[0113] In contrast, the intraocular lenses of Comparative Examples 1 and 2 obtained using a monomer mixture not containing mono(meth)acrylate (A) had copolymer glass transition temperatures of -3.4°C and -9.0°C, tensile break elongations of 148% and 130%, and compressive loads of the support portions of 0.192 mN and 0.171 mN. In this way, the intraocular lenses of Examples 1 to 3 obtained using the monomer mixture containing 45 mol % or more and 70 mol % or less of mono(meth)acrylate (A) have sufficient flexibility and elongation, and have a high compression load of the haptics, so that it is considered that the stability in the eye is improved compared to conventional 1P type intraocular lenses. In addition, the compression load of the haptics is lower than that of conventional 3P type intraocular lenses, so that it is easy to handle.

[0114] (Examples 4 to 10) An intraocular lens was produced in the same manner as in Example 1 above, except that a monomer mixture solution having the composition shown in Table 6 was prepared. Table 6 below shows the composition of the monomer mixture, as well as the results of measurements of the copolymer's glass transition temperature, water content, compressive load of the support, refractive index, tensile elongation at break, compressive load of the optical part, and glistening / whitening.

[0115] [Table 6]

[0116] In Table 6, the units of the contents of the monomers and polymerization initiators are mol% in the upper row and % by mass in parentheses in the lower row. The content of the polymerization initiator (G) is expressed as a percentage relative to the total amount of moles (100 mol%) or the total amount of mass (100 mass%) of the monomers (A) to (D). As shown in Table 6, the intraocular lenses obtained in Examples 4 to 10 have sufficient flexibility and elongation, and also have a high compressive load at the support portion, and are therefore considered to have improved stability within the eye compared to conventional intraocular lenses.

[0117] (Example 11, Comparative Example 3) An intraocular lens was produced in the same manner as in Example 1, except that a monomer mixture solution having the composition shown in Table 7 was prepared. Table 7 below shows the composition of the monomer mixture, as well as the results of measurements of the copolymer's glass transition temperature, water content, compressive load of the support, refractive index, tensile elongation at break, compressive load of the optical part, and glistening / whitening.

[0118] [Table 7]

[0119] In Table 7, the units of the contents of the monomers and polymerization initiators are mol% in the upper row and % by mass in parentheses in the lower row. The content of the polymerization initiator (G) is expressed as a percentage relative to the total amount of moles (100 mol%) or the total amount of mass (100 mass%) of the monomers (A) to (C) and (H). As shown in Table 7, the intraocular lens obtained in Example 11 has sufficient flexibility and elongation, and also has a high compressive load at the support portion, and is therefore considered to have improved stability within the eye compared to conventional intraocular lenses.

[0120] On the other hand, the intraocular lens of Comparative Example 3 obtained using an intraocular lens material containing a tetrafunctional (meth)acrylate (H) having an ethylene oxide group had an extremely low tensile breaking elongation value due to the large number of crosslinking points, and the compressive load of the support was lower than that of the intraocular lens of Example 11. Furthermore, when a compressive load test of the optical part was performed, the optical part broke into two when folded to 3 mm. Therefore, the intraocular lens of Comparative Example 3 was not suitable as an intraocular lens that is folded small and inserted into the eye.

[0121] (Comparative Examples 4 to 8) A monomer mixture solution having the composition shown in Table 8 was prepared, heated to 80° C. in a nitrogen gas circulating oven and maintained at 80° C. for 1 hour, then heated to 110° C. and maintained at 110° C. for 2 hours to produce an intraocular lens. The mold used was the same as that used in Example 1. Comparative Example 9 A monomer mixture solution having the composition shown in Table 8 was prepared, heated to 80° C. in a nitrogen gas circulating oven and maintained at 80° C. for 2 hours, then heated to 100° C. and maintained at 100° C. for 3 hours to produce an intraocular lens. The mold used was the same as that used in Example 1.

[0122] (Comparative Examples 10 and 11) A monomer mixture solution having the composition shown in Table 8 was prepared, heated to 80° C. in a nitrogen gas circulating oven and maintained at 80° C. for 1 hour, then heated to 110° C. and maintained at 110° C. for 2 hours to produce an intraocular lens. The mold used was the same as that used in Example 1. Comparative Example 12 Except for preparing a monomer mixture having the composition shown in Table 8, an intraocular lens material was produced in the same manner as in Example 1 above.

[0123] [Table 8]

[0124] In Table 8, the units of the contents of the monomers and polymerization initiators are mol% in the upper row and mass% in parentheses in the lower row. The content of the polymerization initiator (G) is expressed as a percentage relative to the total amount of moles (100 mol%) or the total amount of mass (100 mass%) of the monomers (A) to (E) and (H). As shown in Table 8, the intraocular lens of Comparative Example 4 was produced using an intraocular lens material in which the content of mono(meth)acrylate (A) exceeded the range of the present invention and did not contain mono(meth)acrylate (B). As a result, the glass transition temperature of the copolymer was high, and the intraocular lens of Comparative Example 4 was so hard that it was difficult to fold in half, making it unsuitable as an intraocular lens.

[0125] The intraocular lens of Comparative Example 5 was produced using an intraocular lens material that contained a large amount of mono(meth)acrylate (B) having a high glass transition temperature of the homopolymer, and also contained a crosslinkable monomer (D) and did not contain di(meth)acrylate (C). Because of this, the glass transition temperature of the copolymer was high, and the intraocular lens of Comparative Example 5 was not only too hard to fold in half, but also suffered from glistening, making it unsuitable as an intraocular lens. The intraocular lenses of Comparative Examples 6 and 8 were produced using intraocular lens materials that did not contain mono(meth)acrylate (A). As a result, not only was the glass transition temperature of the copolymer low, but the compressive load of the haptics was also low.

[0126] The intraocular lens of Comparative Example 7 was produced using an intraocular lens material that did not contain mono(meth)acrylate (A) and di(meth)acrylate (C). Therefore, the intraocular lens of Comparative Example 7 had a low compression load at the support and also had glistening, making it unsuitable as an intraocular lens material. The intraocular lens of Comparative Example 9 was produced using an intraocular lens material containing a large amount of monofunctional methacrylate (H) containing an ethylene oxide group instead of di(meth)acrylate (C). Therefore, the intraocular lens of Comparative Example 9 had a low glass transition temperature of the copolymer and a low compressive load of the support.

[0127] The intraocular lens of Comparative Example 10 was produced using an intraocular lens material in which the content of mono(meth)acrylate (A) was below the range of the present invention and which contained a monofunctional methacrylate (H) containing an ethylene oxide group instead of the di(meth)acrylate (C). Therefore, the intraocular lens of Comparative Example 10 not only had a low glass transition temperature of the copolymer, a low tensile breaking elongation, and a low compressive load of the support, but also suffered from glistening, making it unsuitable as an intraocular lens. The intraocular lens of Comparative Example 11 was produced using an intraocular lens material with a content of mono(meth)acrylate (A) below the range of the present invention. Therefore, the intraocular lens of Comparative Example 11 had a low glass transition temperature of the copolymer, a low tensile elongation at break, and a low compressive load of the haptics.

[0128] The intraocular lens of Comparative Example 12 was produced using an intraocular lens material containing diacrylate (H) in which the number of repeating ethylene oxide groups was 9, which is lower than the range of the present invention. For this reason, the intraocular lens of Comparative Example 12 not only had a low compressive load at the support, but also suffered from glistening, making it unsuitable as an intraocular lens.

[0129] (Examples 12 and 13, Comparative Examples 13 and 14) An intraocular lens material was produced in the same manner as in Example 1, except that a monomer mixture solution having the composition shown in Table 9 was prepared.

[0130] [Table 9]

[0131] In Table 9, the units of the contents of the monomers and polymerization initiators are mol% in the upper row and mass% in parentheses in the lower row. The content of the polymerization initiator (G) is expressed as a percentage relative to the total amount of moles (100 mol%) or the total amount of mass (100 mass%) of the monomers (A) to (C). As shown in Examples 12 and 13, when a di(meth)acrylate (C) containing a specified amount or more of polyethylene glycol dimethacrylate (i.e., a di(meth)acrylate (C) containing less than a specified amount of polyethylene glycol-polypropylene glycol dimethacrylate) was used, whitening or glistening did not occur, and other physical properties were also favorable for an intraocular lens material.

[0132] On the other hand, as shown in Comparative Examples 13 and 14, when a di(meth)acrylate (C) containing less than a specified amount of polyethylene glycol dimethacrylate (i.e., a di(meth)acrylate (C) containing a specified amount or more of polyethylene glycol-polypropylene glycol dimethacrylate) was used, whitening or glistening occurred, and the di(meth)acrylate was not suitable as an intraocular lens material. In Comparative Examples 13 and 14, since whitening or glistening occurred, measurements of other physical properties were omitted. [Explanation of symbols]

[0133] 1: intraocular lens, 2: optical part, 3: support part, 31: wide part, 32: tip part, 10: stage, L: total length, D: diameter, W1: width of support part on optical part side, W2: width of support part opposite to optical part

Claims

1. An intraocular lens material, comprising: A mono(meth)acrylate (A) having an aryl group in its molecular structure; a mono(meth)acrylate (B) having an aryl group in its molecular structure, different from the mono(meth)acrylate (A); and a dimethacrylate (C) having an alkylene oxide group in its molecular structure, The homopolymer of the mono(meth)acrylate (A) has a glass transition temperature of 40° C. or higher, and the homopolymer of the mono(meth)acrylate (B) has a glass transition temperature of lower than 40° C.; the content of the mono(meth)acrylate (A) in the intraocular lens material is 45 mol % or more and 70 mol % or less, the total content of the mono(meth)acrylate (A) and the mono(meth)acrylate (B) is 85 mol % or more, and the content of the dimethacrylate (C) is 0.5 mol % or more and 3.5 mol % or less, An intraocular lens material, wherein the dimethacrylate (C) contains a dimethacrylate represented by the following general formula (I) at a ratio of 60 mol % or more: 【Chemistry 1】 [In the formula, X is a methyl group, and n is an integer of 12 or more and 30 or less.]

2. The intraocular lens material according to claim 1, An intraocular lens material, wherein the alkylene oxide group of the dimethacrylate (C) contains an ethylene oxide group.

3. The intraocular lens material according to claim 2, The intraocular lens material, wherein the dimethacrylate (C) further contains a dimethacrylate represented by the following general formula (II): 【Chemistry 2】 [wherein X is a methyl group, n 1 and n 2 are each independently an integer of 4 or more and 15 or less, and m is an integer of 6 or more and 20 or less.

4. The intraocular lens material according to claim 1, An intraocular lens material, wherein the elongation of the polymer of the intraocular lens material at 23° C. is 150% or more.

5. The intraocular lens material according to claim 1, The glass transition temperature of the polymer of the intraocular lens material is 3°C or higher and lower than 17°C.

6. An intraocular lens, An optical section that transmits light; a pair of support parts protruding outward from opposing positions of the optical part and supporting the optical part within the eye; An intraocular lens, wherein both the optical portion and the pair of support portions are made of a polymer of the intraocular lens material according to any one of claims 1 to 5.

7. The intraocular lens according to claim 6, An intraocular lens, wherein the optical portion and the pair of support portions are integrally formed from the polymer.

8. The intraocular lens according to claim 6, An intraocular lens in which, when the pair of support portions are brought closer together so that the maximum separation distance between them is 10 mm from 13 mm, the load measured at each of the support portions is 0.35 mN or more.

Citation Information

Patent Citations

  • Polymerizable composition, acrylic film and optical member

    JP2012077227A

  • Polymer material and intraocular lens

    JP2019210345A

  • Monomers for use in a polymerizable composition and high refractive index polymer for opthalmic applications

    US20160194424A1

  • Intraocular lens, and manufacturing method thereof

    JP2018183197A